(untitled) (Experimental biology, 2024)
This manuscript outlines the current growing sites of the endemic medicinal plant of Central Asia, E. longistipitata. Today, this plant garners significant interest from the global scientific community due to its remarkable anti-tumor, antioxidant, and anti-inflammatory properties. No analysis of herbarium collections had been performed before, so we took the first step to analyze the herbarium of the Botanical Institute in Uzbekistan and the GBIF. More than 100 herbarium labels were studied from 1916 to 2020. Based on the herbarium materials, 37 actual locations of E.longistipitata populations with GPS data were identified. As a result populations were found in the five states – Kazakhstan, Uzbekistan, Kyrgyzstan, Turkmenistan, and Tajikistan. In Kazakhstan E.longistipitata was found in the three growing points located in the western Tien Shan, Pamir-Alay, and Karatau mountain ranges. The research allowed for the refinement and supplementation of information on the distribution range of E.longistipitata in Central Asia.